2018
DOI: 10.1001/jamadermatol.2017.4169
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of the Sentinel Lymph Node Biopsy for High-Risk Squamous Cell Carcinoma of the Skin

Abstract: With recent changes in staging of cutaneous squamous cell carcinoma (SSC), we examine the underuse of the sentinel lymph node biopsy (SLNB) in the management of high-risk SCC. To date, the most important determinant of mortality in SCC is the presence of lymph node metastasis. 1 Recent data have led to an updated staging system for cutaneous SCC proposed by Brigham and Women's Hospital, which emphasizes the presence or absence of high-risk features. This new staging system stratified T staging of SCC tumors ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
7
1
Order By: Relevance
“…SLNB in patients with cSCC must therefore be discussed individually based on the presence of risk factors such as tumor thickness, tumor diameter and desmoplasia. Ahadiat et al demonstrated that SLNB is underutilized for high-risk tumors [ 1 ]. Based on the available data, SLNB should only be considered for patients with high-risk cSCC and should be assessed individually in each case.…”
Section: Discussionmentioning
confidence: 99%
“…SLNB in patients with cSCC must therefore be discussed individually based on the presence of risk factors such as tumor thickness, tumor diameter and desmoplasia. Ahadiat et al demonstrated that SLNB is underutilized for high-risk tumors [ 1 ]. Based on the available data, SLNB should only be considered for patients with high-risk cSCC and should be assessed individually in each case.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of regional lymph node status is important in cancer staging because it determines the prognosis of patients and informs further treatment. Therefore, sentinel lymph node biopsy (SLNB) is routinely performed in many malignant tumors, including melanoma, 1 as well as breast, 2 vulvar, 3 penile, 4 Merkel cell, 5 squamous cell, 6 and sweat gland 7 carcinomas. In addition, SLNB is partially used in esophageal, 8 gastric, 9 and colorectal 10 carcinomas.…”
Section: Introductionmentioning
confidence: 99%
“…In general, there is an underutilization of SLNB and overutilization of CLND with no clear survival benefit of CLND. 16 Multiple studies have demonstrated the use of SLNB in high-risk cSCC. [17][18][19] However, slow adoption is likely related to a lack of standardization and subsequent high false negative rates, 27.3% in one study after exhaustive tissue review.…”
Section: Discussionmentioning
confidence: 99%